Ductal prostate cancer: Clinical features and outcomes from a multicenter retrospective analysis and overview of the current literature. (31st December 2022) - Cozzi, Salvatore; Bardoscia, Lilia; Najafi, Masoumeh; Igdem, Sefik; Triggiani, Luca; Magrini, Stefano Maria; Botti, Andrea; Guedea, Ferran; Melocchi, Laura; Ciammella, Patrizia; Iotti, Cinzia; Gutierrez, Cristina
Abstract: Objective: The aim of the study is to evaluate clinical features and outcomes after different therapeutic strategies for ductal prostate adenocarcinoma (DPC), a rare but aggressive subtype of invasive prostate cancer (PCa) accounting for, in the pure and mixed form, 1% or less and 5% or less, respectively, of all the newly diagnosed PCa. Materials and methods: Patients with a proven diagnosis of DPC undergoing surgery, radiotherapy, and androgen deprivation therapy, alone or in combination, were considered for this multicenter, retrospective study. The study assessed overall survival (OS), disease-free survival (DFS), and age-related disease-specific survival. Results: Eighty-one patients met the study inclusion criteria. Pure DPC was found in 29 patients (36%) and mixed ductal-acinar-PCa in 52 patients (64%). After a median follow-up of 63 months (range, 3–206 months), 3- and 5-year OS rates were 84% and 67%, respectively, and 3- and 5-year DFS rates were 54% and 34%, respectively. There were no significant differences in OS or DFS between the pure and mixed DPC groups. Pure DPC was associated with a higher rate of metastatic disease at onset. Patients 74 years or younger had better disease-specific survival ( p =0.0019). A subgroup analysis favored radiotherapy as the primary treatment for nonmetastatic, organ-confined DPC (3- and 5-year DFS of 80% and 50%, respectively, compared with 5-year DFS of 35% for surgical patients; p = 0.023). Conclusions: Our study found DPC to be rarer, more aggressive, more likely to metastasize, and have a worse prognosis than the common acinar variant, especially in its pure form. Multicenter series are encouraged to obtain large data sets, or propensity score matching analyses with patients with conventional PCa are desirable to understand the best therapeutic approach and improve outcomes.